Platelet Survival in Streptozotocin-Induced Diabetic Rats - Winocour, P D; Laimins, M; Colwell, J A (Thrombosis and Haemostasis, 1984)
Platelet survival in diabetes mellitus may be decreased or normal, and it is not clear whether altered platelet survival is due to a platelet or to a non-platelet defect. Therefore, platelet survival studies were performed at intervals up to 28 days in streptozotocin-induced diabetic and normal rats, using washed platelets from diabetic or normal animals.When compared to platelets from control rats, there was a significant decrease in platelet survival when platelets from 7 and 14 day diabetic rats were injected into normal controls or into diabetic rats.After 28 days of diabetes, platelet survival in diabetic rats was significantly lengthened, whether the platelets came from control or diabetic rats.Conclusions. (1) Shortened platelet survival in the diabetic rat is caused initially by a platelet defect. Later, non-platelet factors become dominant. (2) These findings may help explain reported discrepancies in results of platelet survival in diabetes mellitus.
Keywords: Platelet survival; Diabetes mellitus; Rats